Modern leatherwork for Makers : traditional craft techniques meet CNC and 3D printing - Deagan, Tim (Maker Media, Inc, 2017)
Take leather crafting into the 21st century with this complete guide that marries traditional skills to the latest CNC and 3D printing technologies. Learn how to start making your own leather creations with traditional tools, and then take them to incredible new levels with digital design techniques. Leatherworking is one of humankind's oldest skills and remains a fun and exciting way to make great-looking wearables, accessories, and cosplay items. 3D printers and even hobbyist-class CNC machines have created fantastic new opportunities for new directions in this popular hobby. The book is perfect for makers new to leatherworking, as well as experienced leatherworkers who want to understand how to integrate new digital fabrication tools into their workbench. Written by an experienced leatherworker and programmer, this is a resource that makers will turn to again and again. Highlights: First comprehensive reference on applying digital design techniques to leatherwork Provides both a reference manual and a project guide Includes traditional techniques like cutting, stamping, tooling and dyeing leather Introduces novices and experienced leatherworkers to cutting-edge digital tools Every project has been real-world tested Opens up exciting new project areas for makers This book provides valuable reference and how-to information for makers interested in leatherworking but who have no prior experience, for experienced leatherworkers who want to extend their knowledge to include new digital tools, and for 3D printing and CNC enthusiasts who want to include a new material in their repertoire. Leatherworking is a hobby that is enjoyed by a wide range of people from middle school through adulthood and can be incorporated into a variety of other kinds of projects, from clothing design and costuming to carrying cases and furniture.